Linguistic, Stylistic, and Discursive Features of the "Yash Turkistan" Journal (Herald of Journalism, 2025)
The present paper is interested in linguistic, journalistic, and ideological features of the Yash Turkestan journal, issued in emigration within the first half of the twentieth century. From 1929 to 1939, when Mustafa Shokay was its editor in Berlin, the journal expressed a different point of view against colonial policy of Soviet power. It tried to preserve the national character of the Turkestan nations and to promote the idea of independence. The main aim of the present study is to examine the vocabulary, grammar, and style of the publication so that it can be ascertained how it impacted national consciousness and identify its political communication strategies.The merit of the research lies in the consideration of information wars in the early twentieth century. This contributes to better comprehension of present-day issues of information security and ideological approaches. Historical-philological, discursive, linguo-stylistic, comparative, and content-analysis methods are used by the study. The study focuses on the analysis of different layers of vocabulary, including Chagatai, Turkic languages, Arabic-Persian, Ottoman, and Western European words. It also discusses grammatical features, such as archaic Turkic morphology and morphological interference, syntactic structures like complex sentences and concise journalistic styles, and rhetorical devices like appeals, metaphors, and controversial devices.The evidence proves that Yash Turkestan was not only a vehicle for upholding national identity and historical memory but also a political forum for émigré journalism. The journal opposed Soviet policies of assimilation, solidified the cultural and linguistic connections of the Turkic people, and promoted autonomy. The academic importance of this book is that it presents a fresh understanding of émigré journalism from Turkestan and documents the development of journalistic discourse. Its applicability stems from its employment of the experience in using this history to explain contemporary information conflicts and national identity issues.
Keywords: Yash Turkistan, Mustafa Shokay, émigré press, style of Yash Turkistan.